Study on Public Transport Modal Split as a Smart Growth Tool for New City Centre of Bratislava - Tibor Schlosser; Peter Schlosser; Silvia Cápayová; Dominika Hodáková; Andrea Zuzulová (Novel Perspectives of Engineering Research Vol. 4, 2021)
The main objective of this chapter is to describe the strategy for development of the public transport terminals in the city of Bratislava, Capital of Slovak Republic. In Bratislava, there is a huge development boom from the Danube river bank and on the edge of the Old City, where is risen up a new down town of the city. The territory specified will have around 20 high-rises with different function and there will be more than 22 000 new parking spaces together will app. 2 mil. m2 of new activities. The city position in this issue must consist of systematic regulation of build-out in order to reach contemporary modern conception of forming so called „smart cities“– sustainable living and sustainable mobility. Nowadays, the reality is that, we have saturated flows on the street network around the contact area. In this area a new bus station is built, which will influence an existing public transport network created by city bus and trolleybus network. For changing the modal split toward better using the public transport (PT), there is a complex of technical studies to realize around the centre a new tramway lines connecting the operated tramway network in Bratislava. The article deals with the suburb terminal in city of Bratislava, which is a central BUS station directly in this new city centre (just realized and put in operation to the end of 2021) and a smart solution of tramway links around this centre. The other main issue is about the methods of the traffic surveys and results of traffic model, which will be used not only for the prognosis scenarios of dynamic traffic flows but also for changing the modal split for the public transport to reflect the new tram routes. The results of technical studies and possible discussion on put inside this area a modern nonconventional elevated automatic public transport system is an open deal. The appraisal of saturated traffic flows, new traffic form investment and the bus station together with a huge city PT lines create a methodology of traffic modelling for improving the operation of the territory with designing the new tramway lines as a form of sustainable mobility. Some tools for decision making and steps for realization will be shown. The main issue is to change the modal split for PT. There are identifying opportunities to improve the attractiveness of public transport, together with suburban bus service (SBS), thus providing for its precedence over individual car traffic in the city of Bratislava (Fig. 1) and its agglomeration in the Bratislava region. The solution is shown how is possible to be a part of the integrated public transport services possibility to operate regular all days’ mobility problems in the city and not only to cover the rush hours. Behind is an overview of 5 years work of traffic engineers and planners to keep clear systematic approach and solutions with developers and municipality administration.